Pengaruh Time Budged Pressure Dan Skeptisisme Profesional Auditor Terhadap Kualitas Audit - Miranty Eka Oktavia; Herlina Helmy (Universitas Negeri Padang, 2019)
The research aims to know the: Influence of time budged pressure and skepticism of auditors to audit quality. The population in this research were Inspectorate of West Sumatra Provinc. The sample is determined by total sampling method, that all apparaturs of Inspektorate of West Sumatera Province. The data used in this research is primary data. This research used quetionnaires instrument as much as 32 respondents. Data analysis technique used is multiple linear regression. The result showed that: (1) Time budged pressure has significant negative effect on audit quality, where the tcount -2,268 < ttable 2,048407 at sig 0,031 < α 0,05, (2) skepticism didn’t significant effect on audit quality, the tcount 0,442 < ttable 2,048407 in sig 0,662 > α 0,05.